Isolation and Culture of Neonatal Murine Primary Cardiomyocytes. Issue 7 (21st July 2021) - Ravi, Venkatraman; Jain, Aditi; Taneja, Arushi; Chatterjee, Kaushik; Sundaresan, Nagalingam Ravi
Abstract: The cardiomyocyte is the main cell type in the heart responsible for its contractile function. Culturing primary cardiomyocytes from mammalian sources to study their function remains challenging as they are terminally differentiated and cease to multiply soon after birth. The major technical hurdles associated with primary cardiomyocyte culture include attaining high yields, obtaining healthy/viable cells that show spontaneous contractions upon culture, and avoiding contamination by non‐myocyte cardiac cell types such as fibroblasts and endothelial cells. The yield and the quality of the cardiomyocytes obtained are impacted by a variety of factors, such as the purity of the reagents, composition of the digestion mixture, the digestion conditions, and the temperature of the tissue during different steps of isolation. Here, we provide a simplified workflow to isolate, culture, and maintain neonatal primary cardiomyocytes from rats/mice in culture dishes, which can then be used to study, for instance, cardiac hypertrophy and drug‐induced cardiotoxicity. © 2021 Wiley Periodicals LLC. Basic Protocol : Isolation and culture of primary cardiomyocytes from rat/mouse pups Support Protocol : Coating of tissue culture plates with extracellular matrix substrates for efficient cardiomyocyte attachment